Comparison of efficacy of apremilast versus methotrexate in patients with moderate to severe chronic plaque psoriasis - Khalid, Amna; Ghias, Aisha; Shahbaz, Usama; Kiran, Rutaba; Hussain, Abid; Aman, Shahbaz (Journal of Pakistan Association of Dermatologists, 2024)
Objective To compare the efficacy of apremilast versus methotrexate in patients with moderate to severe chronic plaque psoriasis. Â Methods Comparative Experimental Study, which was conducted in Department of Dermatology, Mayo Hospital Lahore. Total 112 patients enrolled after informed consent and divided into two groups. Group A received apremilast 30mg twice daily from day 6 onwards (titrating the dose in the first five days) and Group B given methotrexate 0.3-0.5mg/kg orally. Efficacy assessed by reduction in PASI score comparing baseline with score at end of 12 weeks. Â Results Reduction in PASI score from baseline 24.58Â±5.17 to 9.90Â±4.18 at the end of 12 weeks (efficacy 47.3%) observed in Group A, while in Group B, PASI score reduced from 25.38Â±8.41 to 12.94Â±4.95 (efficacy 21.80%). Adverse effects for both groups were minimal. Â Conclusion Both apremilast and methotrexate are good treatment options and highly effective in treating chronic plaque psoriasis. However, apremilast showed greater efficacy and reduction in PASI score as compared to methotrexate. Â